Conceptualization of Water Flow Pathways in Agricultural Terraced Landscapes. (11th August 2017) - Preti, Federico; Guastini, Enrico; Penna, Daniele; Dani, Andrea; Cassiani, Giorgio; Boaga, Jacopo; Deiana, Rita; Romano, Nunzio; Nasta, Paolo; Palladino, Mario; Errico, Alessandro; Giambastiani, Yamuna; et al.
Abstract: Agricultural terraces are often subject to degradation issues related to water movement. A better understanding of the main hydrological processes that govern surface and subsurface water flow pathways and that are responsible for terrace failure and dry‐stone wall collapse is essential for appropriate water resource management and rural landscape maintenance in terraced areas. However, a clear conceptualization of different hydrological functioning related to wall instability issues is still missing. In this study, we monitored a terrace system in a hilly site of central Italy cultivated with vineyards. We adopted a multidisciplinary approach based on soil analysis, different geophysical techniques, hydrological monitoring, high‐resolution grid terrain analysis and field experiments (infiltration and flooding tests) aiming to: (i) obtain new information of terrace soil and subsoil structure; (ii) test the hypothesis on wall instability based on the formation of preferential flow and water accumulation behind the wall; and (iii) develop a conceptual model of water circulation in agricultural terraces. Our results indicate that terrace soil was highly heterogeneous, including discontinuities and piping systems that facilitated a rapid infiltration and the development of fast subsurface flow. Groundwater rise did not occur, as observed in other terraced sites, but infiltrated water accumulated behind dry‐stone walls, increasing pore water pressure and inducing wall bulging and instability. Our findings provided new field evidences of water circulation and led to the definition of a novel paradigm of hydrological functioning of farming terraced systems for addressing more efficient management and maintenance issues in these vulnerable landscapes. Copyright © 2017 John Wiley & Sons, Ltd.